2015
DOI: 10.1021/acs.jpca.5b07713
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Catalytic Reduction Mechanism of NO by CO on Tetrahedral Rh4 Subnanocluster

Abstract: The catalytic mechanism of 2NO + 2CO → N2 + 2CO2 on Rh4 cluster has been systematically investigated on the ground and first excited states at the B3LYP/6-311+G(2d),SDD level. For the overall reaction of 2NO + 2CO → N2 + 2CO2, the main reaction pathways take place on the facet site rather than the edge site of the Rh4 cluster. The turnover frequency (TOF) determining transition states are characteristic of the second N-O bond cleavage with rate constant k4 = 1.403 × 10(11) exp (-181 203/RT) and the N-N bond fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Another important example is the theoretical study presented by Rempel et al, which showed that NO dissociation is accelerated on a stepped Rh(111) surface . Recently, many DFT calculations have been reported on NO reduction by small Rh clusters, which have shown that these clusters are advantageous in the NO dissociation step. …”
Section: Introductionmentioning
confidence: 99%
“…Another important example is the theoretical study presented by Rempel et al, which showed that NO dissociation is accelerated on a stepped Rh(111) surface . Recently, many DFT calculations have been reported on NO reduction by small Rh clusters, which have shown that these clusters are advantageous in the NO dissociation step. …”
Section: Introductionmentioning
confidence: 99%
“…All density functional theory (DFT) calculations were conducted using Gaussian 09 program with the Lee–Yang–Parr correlation functional (B3LYP). , The basis set of Stuttgart/Dresden (SDD) and corresponding effective core potential (ECP) were employed for the Rh atoms, and 6-311+G­(2d) was used for N atoms, , namely B3LYP/6-311+G­(2d), SDD. The generalized gradient approximation (GGA) methods with the B3LYP functional have been proven to provide accurate energetic and geometric results for transition metals and nitrides. , Vibrational frequency calculations were performed to ensure that the reaction intermediates and transition states (TSs) have zero and one imaginary frequency, respectively. The corrections of zero-point energy were included for the energy analysis, and each imaginary frequency of the TSs was examined to ensure the vibration corresponds to the reaction pathway.…”
mentioning
confidence: 99%
“…The generalized gradient approximation (GGA) methods with the B3LYP functional have been proven to provide accurate energetic and geometric results for transition metals and nitrides. 72,73 Vibrational frequency calculations were performed to ensure that the reaction intermediates and transition states (TSs) have zero and one imaginary frequency, respectively. The corrections of zeropoint energy were included for the energy analysis, and each imaginary frequency of the TSs was examined to ensure the vibration corresponds to the reaction pathway.…”
mentioning
confidence: 99%
“…In these three technologies, the key step is the decomposition of adsorbed NO to produce adsorbed N 2 O. The N 2 O+CO reaction in CO-SCR is faster than the isolated N 2 O+CO reaction over Rh/Al 2 O 3 by an order of magnitude [16]. In CH 4 -SCR, the activation of the C-H bond in CH 4 serves as a rate determining step of the reaction of NO removal by CH 4 [17].…”
Section: Introductionmentioning
confidence: 99%